A scanning electron microscopy study of the seed and post-seminal development in Angelonia salicariifolia Bonpl. (Scrophulariaceae) - Moro, F. V.; Pinto, ACR; Dos Santos, J. M.; Damiao, C. F. (Academic Press Ltd, 2001)
The external morphology of seeds and post-germination developmental stages of Angelonia salicariifolia Bonpl. (Scrophulariaceae) were investigated using scanning electron microscopy. Some structural features of the seed exotesta and seedling in Angelonia are presented for the first time and are of potential taxonomic value for this neotropical genus. The seeds are very small (0.9-1.7 mm long and 0.5-0.9 mm wide), ovate, with a reticulate-crested exotesta, reticules arranged uniformly in longitudinal rows, with a high density of microcilia-like projections on the cell wall of the reticule base and on the edge of the crests. The hilum is located beside the micropyle at the narrow end of the seed. Germination is epigeal. During germination the radicle develops, followed by elongation of the hypocotyl and primary root. At this stage dense root hairs develop on the lower part of the hypocotyl. The apical bud-located between the cotyledons-begins to develop after the cotyledons have unfolded. The cotyledons are equal in size, sessile and ovate. The seedlings have two types of trichomes, one characteristic of the cotyledons and first pair of leaves (glandular, sessile, four-celled head with quadrangular shape) and the other characteristic of the hypocotyl and epicotyl (stalked, erect, elongate and three-celled with dome-shaped unicellular head). (C) 2001 Annals of Botany Company.
Keywords: seed morphology; exotesta-ornamentation; micromorphology; post-seminal stages; seedling; trichomes; SEM; Angelonia salicariifolia Bonpl.; Scrophulariaceae